Systematic approaches for synthesis, design and operation of biomass-based energy systems - Murugappan, Viknesh Andiappan (2016)
A biomass-based energy system (BES) is a utility facility which produces cooling, heat and power simultaneously from biomass. By having a BES installed on-site, industrial processes can reduce energy costs by locally producing heat, cooling and power for process and work place requirements. However, several barriers have hindered development of BESs in the energy industry. These barriers include doubts over its operational uncertainties (e.g., seasonal biomass supply, equipment reliability, etc.), the misconception that generating energy from biomass is only a marginal business and the lack of successful cooperative partnerships within the industry. According to literature, such barriers are due to the lack of frameworks that address design aspects and demonstrate the economic viability of a BES.